1994
DOI: 10.1001/archsurg.1994.01420280024003
|View full text |Cite
|
Sign up to set email alerts
|

Second Renal Transplantations

Abstract: Health care policy reviewers should clearly distinguish the prospects for successful second renal transplants from the outcomes of extrarenal retransplantation. Moreover, because excellent second-renal allograft survival is attainable and comparable to primary-renal allograft survival and because the costs are comparable, restricting suitable patients to subsequent lifelong dialysis becomes unethical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…For such patients, repeat transplantation provides better long-term survival and improved quality of life compared to remaining on dialysis, although these studies have only focused on second transplants (17-19). We herein report the analysis of the UNOS experience evaluating outcomes of 3KT and we demonstrate that in selected patients, a third kidney transplant provides significant patient survival advantage over the waitlist while offering a slightly reduced graft outcome compared to first kidney transplants.…”
Section: Discussionmentioning
confidence: 99%
“…For such patients, repeat transplantation provides better long-term survival and improved quality of life compared to remaining on dialysis, although these studies have only focused on second transplants (17-19). We herein report the analysis of the UNOS experience evaluating outcomes of 3KT and we demonstrate that in selected patients, a third kidney transplant provides significant patient survival advantage over the waitlist while offering a slightly reduced graft outcome compared to first kidney transplants.…”
Section: Discussionmentioning
confidence: 99%
“…9,17,18 Nevertheless, kidney transplant patients, including recipients with kidney retransplant, are heterogeneous and there are many factors, including recipient, donor, and transplantrelated characteristics, that can result in varying outcomes. [2][3][4][5][6]19,20 Machine learning (ML), a subfield of artificial intelligence, has been applied to create clinical decision support tools and individualize patient care, including in kidney transplantation. [21][22][23][24][25][26] Studies have demonstrated that unsupervised ML consensus clustering can be utilized to discover novel data patterns and distinct subtypes, [27][28][29] and ultimately distinguish them into clinically meaningful clusters.…”
Section: Data From the United States Renal Data System And Canadianmentioning
confidence: 99%
“…As a result, some kidney transplant centers have lower kidney retransplant rates with highly selective criteria for retransplantation 9,17,18 . Nevertheless, kidney transplant patients, including recipients with kidney retransplant, are heterogeneous and there are many factors, including recipient, donor, and transplant‐related characteristics, that can result in varying outcomes 2–6,19,20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation